Peningkatan Kapasitas Pengusaha Mikro dengan Pelatihan Pengelolaan Keuangan : (IBM pada Usaha Mikro Kecamatan Kembaran, Kabupaten Banyumas) - Tiara Pandansari; Erna Handayani; Ira Hapsari Hapsari (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
Micro businesses are important amidst the problems of unemployment and economic problems in society. Banyumas Regency, especially in Kembaran District, has more than 3,084 micro-enterprises which really need attention and support from the government, community institutions, especially universities. There are many challenges faced by micro entrepreneurs, both in terms of capital, marketing and management. Limited human resources and management, especially in terms of financial management, is one of the focuses that requires assistance from universities. Therefore, this community service activity is aimed at increasing awareness, understanding and knowledge of micro business financial management with the ultimate aim of improving business performance. The training is not just an introduction, but also practice in using financial management formats with simple Excel-based applications.